Letter from Bruce C. Crowin - Bruce C. Crowin:::::: (1978)
This February 3, 1978 letter from Bruce C. Corwin of the California Democratic Party (Southern California) thanks Councilwoman Jane Tolmach for her contribution to the Madale L. Watson Luncheon. The letter notes that the event supports a comprehensive internship program designed to help young people better understand the workings of the Democratic Party.